2009
DOI: 10.2140/apde.2009.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Heat-flow monotonicity of Strichartz norms

Abstract: Our main result is that for d = 1, 2 the classical Strichartz norm e is f Lassociated to the free Schrödinger equation is nondecreasing as the initial datum f evolves under a certain quadratic heat flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 17 publications
3
77
0
Order By: Relevance
“…Later on, in 2008, Carneiro [5] and Bennett, Bez, Carbery and Hundertmark [3] gave alternative proofs for these cases, including in addition the new case (p, q, d) = (4,8,1). All these proofs, although shedding new light at the problem via different angles, heavily rely on the crucial fact that p = 2k and q = 2kℓ for some integers k ≥ 2 and ℓ ≥ 1.…”
Section: Conjecture 1 a Function F (X) Maximizes (11) If And Only Imentioning
confidence: 99%
“…Later on, in 2008, Carneiro [5] and Bennett, Bez, Carbery and Hundertmark [3] gave alternative proofs for these cases, including in addition the new case (p, q, d) = (4,8,1). All these proofs, although shedding new light at the problem via different angles, heavily rely on the crucial fact that p = 2k and q = 2kℓ for some integers k ≥ 2 and ℓ ≥ 1.…”
Section: Conjecture 1 a Function F (X) Maximizes (11) If And Only Imentioning
confidence: 99%
“…To verify it, it seems natural to first compute S N −1 and then to use a perturbation argument to establish (1.2). In fact, by a remarkable work of Foschi [14] (see also [21,5]), the value of S N −1 is known for N = 2 and N = 3. We cite the following conjecture from [14]; see also [21].…”
mentioning
confidence: 99%
“…We are interested in determining whether there exists a maximizing function u 0 with u 0 L 2 = 1 for which Bennett et al [2008] and Shao [2009]. We set…”
Section: The Linear Profile Decomposition For the Airy Equation 87mentioning
confidence: 99%
“…Recently, Carneiro [2008] proved a sharp Strichartz-type inequality by following the arguments in [Hundertmark and Zharnitsky 2006] and found its maximizers, which derives the same results in [Hundertmark and Zharnitsky 2006] as a corollary when d = 1, 2. Very recently, Bennett et al [2008] offered a new proof to determine the best constants by using the method of heat-flow. Shao [2009] showed that a maximizer exists for all nonendpoint Strichartz inequalities and in all dimensions by relying on the recent linear profile decomposition results for the Schrödinger equations.…”
Section: The Linear Profile Decomposition For the Airy Equation 87mentioning
confidence: 99%